1999
DOI: 10.1021/ja981397y
|View full text |Cite
|
Sign up to set email alerts
|

Upper Excited State Photochemistry:  Solution and Gas Phase Photochemistry and Photophysics of 2- and 3-Cyclopropylindene1

Abstract: The cyclopropylcarbinyl radical rearrangement has been used to probe the photochemistry and photophysics of S2 and S1 in 2-cyclopropylindene (2CPI) and 3-cyclopropylindene (3CPI). Studies in solution and the gas phase are described. Population of S2 with 254 nm light excitation in the gas phase produces the anticipated ring expansion products 2,3,3a,8-tetrahydrocyclopenta[a]indene (1, Φ 1 = 0.1) and 1,3,3a,8-tetrahydrocyclopenta[a]indene (2, Φ 2 = 0.06) from 2CPI and 3CPI, respectively (Scheme ). Direct exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…They can proceed along different routes because in the gas phase the high-energy electronic and vibrational states can live longer without rapid solvent-induced radiationless deactivation. Particularly, the very distinct differences between absorption and excitation spectra and also the latter spectra recorded at different wavelengths were observed for alkylindenes and dihydronaphthalenes . The effects of high-energy excitation can be found in these reactions on the condition that their rates compete with the IC relaxations to S 1 state.…”
Section: Photochemistry From S N (Or From S1 M ) Statesmentioning
confidence: 92%
“…They can proceed along different routes because in the gas phase the high-energy electronic and vibrational states can live longer without rapid solvent-induced radiationless deactivation. Particularly, the very distinct differences between absorption and excitation spectra and also the latter spectra recorded at different wavelengths were observed for alkylindenes and dihydronaphthalenes . The effects of high-energy excitation can be found in these reactions on the condition that their rates compete with the IC relaxations to S 1 state.…”
Section: Photochemistry From S N (Or From S1 M ) Statesmentioning
confidence: 92%
“…Indene, however, is characterised by a poor fluorescence signal (f around 0.005), because its excited states are described as biradicals. [25] Moreover, high level computational studies have simulated the potential energy curve of the excited state looking for conical intersections between S 1 and S 0 to account for the non-radiative processes of indene. [26] They found that the main mechanism involved is a fast and efficient internal conversion process.…”
Section: Fluorene-bodipy Derivativesmentioning
confidence: 99%